Answer:
x = 5/3
y = -8/3
Explanation:
To solve y = 2x - 6 substitute the y for -x - 1 and solve for x.
-x - 1 = 2x - 6 Now you can solve this like a regular inequality. Start by subtracting 2x on both sides.
-3x - 1 = -6 Now add 1 to both sides
-3x = -5 Divide by -3 on both sides
x = 5/3 (the negatives cancel and become positive)
Because you have x, you can go back and properly solve for y. Substitute x for 5/3
y = 2(5/3) - 6 Simplify the right side to get your answer.
y = 10/3 - 6 In order to subtract 6, you first have to convert it to a fraction with a denominator of 3. To do this, put 6 over 1 (6/1) then find the least common denominator of 3 and 1, which is 3. Now multiply 1 by 3 and 6 by 3 to get 18/3
y = 10/3 - 18/3
y = -8/3
I hope this helped :)